Commemorative Issue to Celebrate the Life and Work of Prof. Roger W.H. Sargent - Gani, Rafiqul; Cameron, Ian (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book celebrates the life, work and influence of Professor Roger W.H. Sargent of Imperial College London. It does so through a range of original contributions that span the wide academic and industry interests of Professor Sargent. Roger Sargent passed away in late 2018, but his legacy lives on through his enormous academic tree, which traces to the early 1960s. That huge body of work has also had significant impacts on industrial practices. Roger was regarded as "the father of Process Systems Engineering (PSE)". This area of Chemical Engineering continues to influence the modelling, design, control, optimization and integrated performance of industrial and related processes. This book highlights some of those impacts and the ongoing importance of PSE in helping to solve some of the grand challenges of our time.